Parasitic myelopathy by Gurltia Paralysans (Veterinary Science, 2017)
Parasitic myelopathy by Gurltia paralysans is, apparently,a South American disease, but little is known about it. It isa medullary disorder caused by a parasite that in its adultform, it is lodged in the spinal veins of cats causing a hemorrhageby suffusion that compromises the spinal cord in avariable way.It has been proposed that domestic cats are accidentalguests, and that small wild cats such as the huiña cat (Felisguigna) in Chile, or the cat of the pampas (Felis geoffroyi)in Brazil and Argentina, are the definitive hosts, housingthe parasite in the lung. Cats are likely infected by ingestingsmall lizards. The affected animals present typical signsof chronic myelopathy, with varying degrees of affection,from ataxia to severe paraparesis, depending on the timeof evolution. The main lesions are between T10 and L2,with projection up to L5-L6. The affected cats always livein rural areas, and this parasitosis has not been diagnosedin any urban area. The diagnosis is based on the clinicalhistory of slowly progressive chronic myelopathy and thehabitat of sick cats. Recently a PCR technique has been developedthat allows the identification of parasitic DNA inthe CSF of the affected cats. The treatment is based on theapplication of ivermectin, and it is most effective if it is implementedearly.
Keywords: ataxia; myelopathy; paraparesis; cats